Pain Status and Disability in Activities of Daily Living Among Older Adults in China: Evidence From CHARLS 2020 - Jingjing Chu; Luxi Weng; Wen Jin; Xi Yin; Qin Xu; Zherong Xu (Pain Research and Management, 2025)
Conclusions: Pain status, especially multisite pain, is significantly associated with BADL and IADL disabilities in older Chinese adults. Although causality cannot be inferred due to the study’s cross-sectional design, these findings underscore the importance of addressing pain alongside other health and psychological factors when developing strategies to support functional independence in aging populations.